C08 Caffeine is a modifier of age at onset in Huntington's disease. (16th November 2010) - Duru, C; Simonin, C; Richard, F; Hincker, P; Génin, M; Charles, P; Youssov, K; Burnouf, S; Azulay, J-P; Verny, C; Tranchant, C; Goizet, C; et al.
Abstract : Background: Phenotypic expression is variable in Huntington's disease (HD). Mutation in the IT15/HD1 gene statistically predicts for the age at onset (AAO), but on an individual basis, repeat length accounts for about 60% of its variance supporting the fact that 40% of the remaining variance is due to additional genetic and/or environmental factors. Association of AAO with polymorphisms located in different genes (ex: ADORA2A) has been previously reported. In contrast, whether environmental factors are also able to influence AAO remain unknown. Caffeine is a non-selective antagonist of A2A receptors, selectively localised on striatal medium spiny neurons expressing enkephalin and dopaminergic D2 receptors, known to be the most vulnerable ones in HD. Interestingly, modulation of A2A receptors influence the pathophysiological outcome in experimental models of HD. Aims: To determine the impact of caffeine on the AAO (primary endpoint) and the rates of functional, motor and cognitive decline (secondary endpoints) in HD patients. Methods: 58 HD patients were included from eight sites over a 6 month period. Information about caffeine consumption was collected with a validated self-questionnaire. All patients were evaluated using the Unified Huntington's Disease Rating Scale. Factors influencing AAO were examined using a stepwise regression analysis. After adjustment of CAG repeat length, subjects were categorised into three group and we compared the mean of AAO between low end high consumers. Results: We found a significant correlation between AAO and caffeine intake (r2=0.041; p=0.016): the highest caffeine intake was associated with the earlier AAO. Also, we demonstrated that caffeine influenced AAO with an advanced AAO of 6.9 years in high consumers compared with low consumers. However, we failed to demonstrate a relation between caffeine intake and the rate of functional, motor and cognitive decline. Conclusion: Our findings suggest that caffeine could be the first environmental modifier of AAO in HD. It could have an important therapeutic impact as the modulation of A2A receptors may represent new strategies for treating HD.